Analysis of The Duai Boe Traditional Ceremony of Bajo Tribe In Parumaan Village - Rani Rani; Nur Syamsiyah Ekhsan; Rikardus Nasa (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to describe the process in the Duai Boe traditional ceremony and analyze the meaning of the symbols used in the Duai Boe traditional ceremony. The researcher used qualitative method. Data collection techniques used in this research are interview and documentation. The results of the research found that there are two stages of the Duai Boe traditional ceremony. The first stages is called Bantang and the second stage is called Paduwai Atowene Ka Boe Tella which is the final stage of Duai Boe traditional ceremony. There are eight symbols used in the Duai Boe traditional ceremony, namely 1) The coconut water symbolizes that in the future the baby can be useful for many people, 2) The rice symbolizes that the mother has performed the Duai Boe ceremony, 3) The ring symbolizes a hope that this child will be attractive like gold, 4) the thread tied around the baby's wrist symbolizes that this baby does not get sick, such as wounds or redness on the wrists, feet, elbows, groin, stomach and neck, 5) money symbolizes as a family thank you to the Sandro for the assistance provided from the beginning of childbirth until the ritual ceremony is complete, 6) knife blade stuck in a cloth has been burnt symbolizes that spirits don't approach and disturb the baby's mother because spirits don't like the smell of burning cloth, 7) The Incense symbolizes calling the spirits of the ancestors to come witness the ritual and are expected to pray for the baby so that what the family hopes for in the future will be achieved.